PHENOMENOLOGY AND APOPHATIC THEOLOGY: THE RECEPTION OF ST DIONYSIUS THE AREOPAGITE IN JEAN-LUC MARION’S THOUGHT / FENOMENOLOGIE ȘI TEOLOGIE APOFATICĂ: RECEPTAREA SF. DIONISIE AREOPAGITUL ÎN GÂNDIREA LUI JEAN-LUC MARION - TURCAN, Nicolae (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2015)
This text analyses the reception of St Dionysius the Areopagite’s apophaticism in Jean-Luc Marion’s thought. After a dispute with Jacques Derrida, who claimed that negative theology returns to affirmations after having passed through negations, Marion reads Dionysius’ apophaticism in the same way the Tradition of the Church did. Hence, he asserts that apophaticism is a third way, beyond affirmations and negations. As Marion’s apology evolves, Dionysius’ influences on his thought appear in concepts such as God without being, distance, and saturated phenomenon. Furthermore, this study argues the role of the human being in apophatic theology. Because of his radical phenomenology of donation, Marion reverses intentionality in counter-intentionality, experience in counter-experience, and subject in adonné. From this point on, the subject/l’adonné seems to have no determinative role for apophatic gnoseology, although Church Tradition always affirmed the importance of faith and virtues for spiritual ascent. The solution proposed in this text makes a distinction between Kant’s transcendental and the conditions of possibility gained by hermeneutics, ascetics, liturgy, and divine grace. L’adonné has no previous Kantian conditions of possibility; however, it can create some conditions of possibility from previous saturated phenomena. These conditions do not jeopardize the excess of the saturation. Acest text analizează receptarea apofatismului Sf. Dionisie Pseudo-Areopagitul de către gândirea lui Jean-Luc Marion. Într-o dispută cu Jacques Derrida, care afirma că teologia negativă revine la afirmații după o trecere prin negații, Marion înțelege apofatismul dionisian la fel cum îl înțelege Tradiția Bisericii. Astfel, el afirmă că apofatismul este o a treia cale dincolo de afirmații și negații. După cum arată apologia lui Marion, influențele lui Dionisie asupra gândirii sale sunt vizibile în concepte precum Dumnezeul fără ființă, distanța și fenomenul saturat. Mai mult, acest studiu argumentează în favoarea rolului omului în teologia apofatică. Datorită fenomenologiei radicale a donației, Marion răstoarnă intenționalitatea în contra-intenționalitate, experiența în contra-experiență și subiectul în adonat. În acest punct, subiectul/adonatul pare a nu avea niciun rol determinant pentru gnoseologia apofatică, deși Tradiția Bisericii a afirmat întotdeauna importanța credinței și virtuților pentru urcușul duhovnicesc. Soluția acestui text oferă o distincție între transcendentalul lui Kant și condițiile de posibilitate câștigate prin hermeneutică, asceză, liturghie și har dumnezeiesc. Adonatul nu are condiții de posibilitate kantiene și anterioare, dar poate crea unele din fenomenele saturate anterioare. Aceste condiții nu periclitează excesul saturației.